2004
DOI: 10.1002/hc.20043
|View full text |Cite
|
Sign up to set email alerts
|

The identification of some novel four‐membered ring cyclic triphosphenium ions in solution

Abstract: The first four-membered ring cyclic triphosphenium ions with carbon substituents (methyl or cyclohexyl) on the outer phosphorus atoms have been identified in solution by31 P NMR spectroscopy. The cyclohexyl derivative in the presence of [SnCl 6 ] 2− as counterion was stable enough for methylation by methyl triflate to be carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The presence of the 'bare' P in a low oxidation state should facilitate oxidation reactions at this centre, and we have shown that direct methylation using excess methyl triflate is possible for many of these ions to form di-ium dications, as depicted in Scheme 1. 10,11 Scheme 1 Direct methylation of cyclic triphosphenium ions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the 'bare' P in a low oxidation state should facilitate oxidation reactions at this centre, and we have shown that direct methylation using excess methyl triflate is possible for many of these ions to form di-ium dications, as depicted in Scheme 1. 10,11 Scheme 1 Direct methylation of cyclic triphosphenium ions.…”
Section: Introductionmentioning
confidence: 99%
“…Small amounts of oxidation products such as the diphosphane monoxide, which gives rise to two doublets, or the diphosphane dioxide, which gives a single resonance, were occasionally detected, particularly for diphosphanes with alkyl substituents, but these did not interfere with formation of the cyclic triphosphenium ions. These were prepared quantitatively in CH 2 Cl 2 solution as described previously [7,8,10,11], from either a 3:2 mixture of the diphosphane and PCl 3 , or a 1:1:1 mixture of the diphosphane, PCl 3 , and SnCl 2 , where the hexachlorostannate(IV) was required. The calculated quantity of a solution of AlCl 3 and t BuCl (1:1) in CH 2 Cl 2 or of triflic acid was added by microsyringe, once formation of the ring had been confirmed spectroscopically.…”
Section: Methodsmentioning
confidence: 99%
“…Protonation of the four-membered ring with cyclo-hexyl substituents 26 (described very recently by us [10]) was also attempted. In this case the ring was freshly prepared from the diphosphane, SnCl 2 , and PCl 3 ; NMR spectroscopy confirmed that it had formed (δ 31 P P B 45.4 (d) 2P, P A −216.1 (t) 1P ppm, 1 J PP 330.9 Hz).…”
Section: Protonations With Triflic Acidmentioning
confidence: 99%
See 2 more Smart Citations